The bifoil photodyne: a photonic crystal oscillator - Lugo, J. E. (Nature Publishing Group, 2014)
Optical tweezers is an example how to use light to generate a physical force. They have been used to levitate viruses, bacteria, cells, and sub cellular organisms. Nonetheless it would be beneficial to use such force to develop a new kind of applications. However the radiation pressure usually is small to think in moving larger objects. Currently, there is some research investigating novel photonic working principles to generate a higher force. Here, we studied theoretically and experimentally the induction of electromagnetic forces in one-dimensional photonic crystals when light impinges on the off-axis direction. The photonic structure consists of a micro-cavity like structure formed of two one-dimensional photonic crystals made of free-standing porous silicon, separated by a variable air gap and the working wavelength is 633 nm. We show experimental evidence of this force when the photonic structure is capable of making auto-oscillations and forced-oscillations. We measured peak displacements and velocities ranging from 2 up to 35 microns and 0.4 up to 2.1 mm/s with a power of 13 mW. Recent evidence showed that giant resonant light forces could induce average velocity values of 0.45 mm/s in microspheres embedded in water with 43 mW light power.